Effect of sirolimus as an immunosuppressive agent on kidney transplantation in patients with diabetes mellitus; a systematic review - Saeedeh Davar; Mohsen Mohammad Rahimi; Maasoumeh Mahdi Akhgar; Sajjad Saei (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Sirolimus is a macrolide and a type of immunosuppressant drug to prevent rejection of transplanted organs. This drug inhibits the activation of T and B lymphocytes and reduces the production of interleukin-2 (IL-2). Objectives: This study aimed to review the effect of sirolimus in kidney transplantation in patients with diabetes mellitus as a systematic review. Materials and Methods: International databases including PubMed, Web of Science and Scopus were considered for search of English articles by 29 June 2019. Twenty-one published articles were finally entered into the study. Keywords were sirolimus, rapamune, rapamycin, diabetes mellitus and kidney transplantation or a combination of them in the title/abstracts. Treatment using a combination of sirolimus and tacrolimus were excluded. Results: There were more than 3244 subjects reviewed in this systematic review including 21 published articles (Total population of 21 articles: 3244 people). Conclusion: According to the results, sirolimus-based immunosuppression for preventing kidney transplantation is effective and has a low-risk in diabetic patients resulting in suitable glucose control.